2004
DOI: 10.1074/jbc.m403832200
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of Ionizable Residues Proximal to the Cytoplasmic Interface of Membrane Spanning Domain 3 of the Multidrug Resistance Protein, MRP1 (ABCC1)

Abstract: The multidrug resistance protein MRP1 is an ATP-dependent transporter of organic anions and chemotherapeutic agents. A significant number of ionizable amino acids are found in or proximal to the 17 transmembrane (TM) helices of MRP1, and we have investigated 6 of these at the cytoplasmic interface of TM13-17 for their role in MRP1 expression and transport activity. were also transport-inactive and no longer bound leukotriene C 4 . In contrast, substrate binding by the transport-compromised E1204L mutant remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 41 publications
2
57
0
Order By: Relevance
“…In addition, because MRP1 can also transport GSH alone or together with substrates such as vincristine (14), and assuming that nucleotides play a common mechanistic role in the transport of different substrates, then these findings could be construed to indicate the presence of two distinct GSH binding sites: one where GSH undergoes transport, and a second where GSH elicits allosteric effects on MRP1 without being translocated across the membrane. Such an idea has been proposed previously on the basis of mutagenesis experiments where the mutation of a single residue prevents GSH transport, yet GSH-stimulated estrone sulfate transport is only mildly affected (50,51), and vice versa (52), 5 but this remains to be directly proven.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, because MRP1 can also transport GSH alone or together with substrates such as vincristine (14), and assuming that nucleotides play a common mechanistic role in the transport of different substrates, then these findings could be construed to indicate the presence of two distinct GSH binding sites: one where GSH undergoes transport, and a second where GSH elicits allosteric effects on MRP1 without being translocated across the membrane. Such an idea has been proposed previously on the basis of mutagenesis experiments where the mutation of a single residue prevents GSH transport, yet GSH-stimulated estrone sulfate transport is only mildly affected (50,51), and vice versa (52), 5 but this remains to be directly proven.…”
Section: Discussionmentioning
confidence: 97%
“…Materials- [14,15,19, (25,26). 4 These basic residues were also localized in the atomic homology models of MRP1 derived by molecular dynamics simulations using the crystal structure of the bacterial lipid transporter MsbA as template (10).…”
Section: Methodsmentioning
confidence: 99%
“…Charged residues are black, and polar residues are shaded gray. The three basic residues mutated in the present study are indicated by asterisks, and a diamond denotes Arg 1131 mutated in a previous study (15).…”
Section: Kinetic Analysis Of [ 3 H]e 2 17␤gmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, site-directed mutagenesis studies have identified a number of mutation-sensitive amino acids with respect to transport and/or binding of LTC 4 . Thus, nonconservative (and in some cases, conservative) substitutions of certain residues located in or proximal to the cytosolic interface of TM6 ( (Haimeur et al, , 2004aCampbell et al, 2004;Koike et al, 2004;Situ et al, 2004;Zhang et al, 2004). However, it is not known whether these amino acids are in direct contact with LTC 4 or whether they have an indirect but critical role in maintaining the architecture of the LTC 4 binding site on the protein, or both.…”
Section: Analyses Of Mrp1mentioning
confidence: 99%